Implementation of Good Corporate Governance and Internal Control Systems on Perceived Quality of Financial Information - Made Rina Permata Dewi; Gayatri (E-Jurnal Akuntansi, 2024)
This study aims to examine empirically the influence of the principles of transparency, accountability, responsibility, independence, fairness/equality and internal control systems. The research data was collected through a questionnaire, the research respondents were the number of employees obtained directly from the head of the finance and general department, employees of the finance section, and employees of the general section at the PERUMDA Air Minum Tirta Mangutama Kabupaten Badung. The method of determining the sample using purposive sampling with a total of 54 respondents. The data analysis technique used in this research is Path Analysis (SEM-PLS). Based on the results of the study, it shows that Transparency; Accountability; Responsibility; Independency; Fairness; Internal Control System have a positive and significant effect on the quality of financial information.